2013
DOI: 10.1111/boc.201300020
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear MMP‐9 role in the regulation of rat skeletal myoblasts proliferation

Abstract: During myoblasts differentiation, MMP-9 that is localised in nuclei might be involved in the processes regulating cell cycle progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Our previous analyses of selected aspects of crushinduced regeneration, 15,16,34,35,45 as well as in vitro differentiation of satellite cells isolated from EDL and soleus muscles 15,46,47 extensively documented existing differences. For example, focusing at the myogenic regulatory factors (MRFs), i.e., MyoD, Myf-5, MRF4, and myogenin, we have shown that they are expressed earlier during fast-twitch EDL muscle repair as compared to slow-twitch soleus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous analyses of selected aspects of crushinduced regeneration, 15,16,34,35,45 as well as in vitro differentiation of satellite cells isolated from EDL and soleus muscles 15,46,47 extensively documented existing differences. For example, focusing at the myogenic regulatory factors (MRFs), i.e., MyoD, Myf-5, MRF4, and myogenin, we have shown that they are expressed earlier during fast-twitch EDL muscle repair as compared to slow-twitch soleus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is involved in various physiological functions, such as tissue remodeling, cellular differentiation (Zimowska et al, 2013), cell-cell contact and cell migration (Kim et al, 2012), the release of cytokines and regulation of growth factor activity (Schonbeck et al, 1998), survival and apoptosis (Kowluru et al, 2011), angiogenesis, inflammation, and signaling (for a comprehensive review of MMP-9 function, see Vandooren et al, 2013; Verslegers et al, 2013). Aside from maintaining tissue homeostasis, MMP-9 plays a role in a range of pathologies (comprehensively reviewed in Rivera et al, 2010; Kaczmarek, 2013).…”
Section: Matrix Metalloproteinase-9mentioning
confidence: 99%
“…The presence of nuclear MMP9 has been documented in several cell types, including human neuroblastoma cells, human endothelial cells (Sinha et al ., ), rodent myoblasts (Zimowska et al ., ) and murine macrophages (Marchant et al ., ). The nuclear MMP9 signal in spermatogonia and cells around the seminiferous epithelium, as illustrated in this study, may be associated with processes such as mitosis that require nuclear matrix degradation, a proposal that requires further investigation.…”
Section: Discussionmentioning
confidence: 99%